2009
DOI: 10.1002/pbc.22291
|View full text |Cite
|
Sign up to set email alerts
|

Functional independence score in hemophilia: A cross‐sectional study assessment of Mexican children

Abstract: BackgroundThe Functional Independence Score in Hemophilia (FISH) is a performance‐based assessment tool used to measure the patients functional ability so far only used in patients with severe hemophilia. Its aim is to determine if FISH is useful in patients with mild and moderate disease.ProcedureIn a cross‐sectional study 90 children 60 hemophilic and 30 sex‐, race‐, and age‐matched healthy males were assessed. Patients between 5 and 16 years of age were selected each patient was evaluated in seven activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
(21 reference statements)
4
17
1
Order By: Relevance
“…In our study, the mean FISH score was 23.32 ± 4.69 (range 13–28).Patients with severe haemophilia had lower FISH scores compared to those with moderate and mild haemophilia (20.5 ± 3.97 vs. 24.7 ± 2.4 in moderate haemophilia and 27.7 ± 0.48 in mild haemophilia). These results are matched with a recent Mexican study [7] where mean FISH score was significantly higher in patients with mild haemophilia (28 ± 0) than in patients with moderate (26.27 ± 2.54; P = 0.004) or severe haemophilia (24.08 ± 4.74; P = 0.0006). Similarly, step climbing, squatting and walking were the most affected activities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the mean FISH score was 23.32 ± 4.69 (range 13–28).Patients with severe haemophilia had lower FISH scores compared to those with moderate and mild haemophilia (20.5 ± 3.97 vs. 24.7 ± 2.4 in moderate haemophilia and 27.7 ± 0.48 in mild haemophilia). These results are matched with a recent Mexican study [7] where mean FISH score was significantly higher in patients with mild haemophilia (28 ± 0) than in patients with moderate (26.27 ± 2.54; P = 0.004) or severe haemophilia (24.08 ± 4.74; P = 0.0006). Similarly, step climbing, squatting and walking were the most affected activities.…”
Section: Discussionsupporting
confidence: 89%
“…haemophilia). These results are matched with a recent Mexican study [7] where mean FISH score was significantly higher in patients with mild haemophilia (28 ± 0) than in patients with moderate (26.27 ± 2.54; P = 0.004) or severe haemophilia (24.08 ± 4.74; P = 0.0006). Similarly, step climbing, squatting and walking were the most affected activities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The self‐reported PedHAL focuses on activities of daily living such as use of transport, self‐care and household tasks, whereas the HEP‐Test‐Q assesses aspects of physical functioning based on motor ability (mobility, strength, coordination and endurance). PedHAL is an internationally recognized instrument with use in clinical trials, yet there is limited published evidence of its use . FISH has also been used internationally in children and adults and has been shown to be a reliable tool for assessing functional ability in CWH compared to normal controls revealing lower limb functional abnormalities (squatting, walking, and step climbing) and functional “independence” in adolescents .…”
Section: Discussionmentioning
confidence: 99%
“…The FISH was found to be highly reliable, with a pooled intraclass correlation coefficient of 0.98. In studies from Mexico [46] and Egypt [47], the FISH was found to discriminate the severity of hemophilia, as well as between patients and healthy controls. The FISH had a good correlation with the WFH clinical score (r = −0.61).…”
Section: Musculoskeletal Outcome: Assessment Of Activities and Functimentioning
confidence: 97%